ANALISIS PEMBUATAN DEM DENGAN MENGGUNAKAN BERBAGAI RAGAM SENSOR (STUDI KASUS : RUMAH SAKIT SALMAN HOSPITAL KABUPATEN SOREANG) - Yasir Falah, Muhammad
DEM (Digital Elevation Model) is a model that represent height of terrain without vegetation and manmade building. The shape of earth surface represented with DEM is needed for analysis in field which need spatial concern such as construction. DEM can be generated from various method such as from terrestrial measurement and remote sensing (satellite imagery, photogrammetry, laser, and radar). The use of different acquisition method affects DEM’s. In this research, DEM from photogrammetry, TLS, and terrestrial (combination of ETS and RTK) were compared. They were evaluated by subtracting the elevation model form each other to see visual difference. DEM is also compared by profile measured by levelling. Difference between profile and the is presented in RMSE, result of RMSE is 0,359, 0,213, and 0,375 metres for photogrammetry, terrestrial (combination of ETS and RTK), and TLS.